Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1038/s41564-018-0164-0
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic-resistant bacteria show widespread collateral sensitivity to antimicrobial peptides

Abstract: Antimicrobial peptides are promising alternative antimicrobial agents. However, little is known about whether resistance to small-molecule antibiotics leads to cross-resistance (decreased sensitivity) or collateral sensitivity (increased sensitivity) to antimicrobial peptides. We systematically addressed this question by studying the susceptibilities of a comprehensive set of 60 antibiotic-resistant Escherichia coli strains towards 24 antimicrobial peptides. Strikingly, antibiotic-resistant bacteria show a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
246
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 312 publications
(263 citation statements)
references
References 66 publications
(113 reference statements)
6
246
0
Order By: Relevance
“…The i-modulon structure is conserved across transcriptomic datasets Each of the five transcriptomic datasets were created using different technologies or generated by different research groups, spanning fifteen years (2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018)(2019). In addition, each 150 dataset contained vastly different experimental conditions and genotypes, such as overexpressed cellular division proteins in the MA-1 dataset 32 , diverse nutritional supplements in the RNAseq-1 dataset, or strains evolved to resist antibiotics in the RNAseq-2 dataset 31 . Although the presence of different conditions in each dataset complicated the identification of consistent i-modulons, many of the i-modulons generated from the five datasets unexpectedly shared similar genes and 155 annotations.…”
Section: Resultsmentioning
confidence: 99%
“…The i-modulon structure is conserved across transcriptomic datasets Each of the five transcriptomic datasets were created using different technologies or generated by different research groups, spanning fifteen years (2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018)(2019). In addition, each 150 dataset contained vastly different experimental conditions and genotypes, such as overexpressed cellular division proteins in the MA-1 dataset 32 , diverse nutritional supplements in the RNAseq-1 dataset, or strains evolved to resist antibiotics in the RNAseq-2 dataset 31 . Although the presence of different conditions in each dataset complicated the identification of consistent i-modulons, many of the i-modulons generated from the five datasets unexpectedly shared similar genes and 155 annotations.…”
Section: Resultsmentioning
confidence: 99%
“…It also informs on the ‘latent resistome’, that is, the collection of genes where a change from native expression level enhances resistance to a particular drug 26 . We applied a sensitive competition assay by monitoring growth of a pooled plasmid library overexpressing all the E. coli ORFs (Figure 1a), as we reported earlier 27 . Specifically, E. coli cells carrying the pooled plasmid collection were grown in the presence or absence of one of the 15 AMPs tested, at a sub-inhibitory concentration that increased the doubling time of the whole population by 2-fold.…”
Section: Resultsmentioning
confidence: 99%
“…Collateral sensitivity was first described as early as 1950s [47] and was recently verified in a series of laboratory evolved resistant strains of E. coli and P. aeruginosa [4850]. It was proposed that collateral sensitivity is a common phenomenon in AMR strains and can be exploited to eradicate clinical resistant strains or reduce resistance development by programming the drug pairs that produce reciprocal collateral sensitivity [39, 51, 52]. However, a recent study reported the lack of collateral sensitivity in clinical P. aeruginosa isolates from the cystic fibrosis (CF) patients [53].…”
Section: Resultsmentioning
confidence: 99%